Abrogation Without Replacement in the Qur’an: Rethinking al-Tadarruj fi al-Tashrī‘ - Chalik, Siti Aisyah; Hardivizon, Hardivizon; Wahyuni, Sri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article critically examines the concept of nasakh (abrogation) in the Qur’an, with a particular focus on cases where a ruling is interpreted as being abrogated without a clearly defined substitute (nasakh bilā badal). Rather than understanding such cases as definitive cancellations, this study proposes that they should be read through the framework of al-tadarruj fi al-tashrī‘ (gradual legislation), which conceives of legal revelation as a phased and pedagogical process aligned with the intellectual and spiritual development of the Muslim community. Using a qualitative library-based research design and critical content analysis, the article re-examines key verses—including Q.S. al-Mujādilah [58]:12–13, Q.S. al-Baqarah [2]:184–185, and Q.S. al-Nisā’ [4]:15—in their historical and exegetical contexts. The findings demonstrate that these transitions reflect deliberate stages of moral and legal formation rather than normative discontinuity. By foregrounding contextual, historical, and maqāṣid-based dimensions of revelation, the study advances a new interpretive model that reconceptualizes nasakh as part of a dynamic and purposive framework of legal development. This approach offers a crucial corrective to rigid classical classifications and contributes to contemporary Qur’anic studies by affirming the continued relevance of divine law in addressing shifting socio-historical realities.